2013
DOI: 10.1371/journal.pone.0056285
|View full text |Cite|
|
Sign up to set email alerts
|

Social Sector Expenditure and Child Mortality in India: A State-Level Analysis from 1997 to 2009

Abstract: BackgroundIndia is unlikely to meet the Millennium Development Goal for child mortality. As public policy impacts child mortality, we assessed the association of social sector expenditure with child mortality in India.Methods and FindingsMixed-effects regression models were used to assess the relationship of state-level overall social sector expenditure and its major components (health, health-related, education, and other) with mortality by sex among infants and children aged 1–4 years from 1997 to 2009, adju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 23 publications
3
17
0
Order By: Relevance
“…None of the earlier Indian studies have treated public health spending as an endogenous variable. [16][17][18] The limitations of our study must also be noted. An obvious limitation of our study is that we could not control for household wealth in the regression analysis.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…None of the earlier Indian studies have treated public health spending as an endogenous variable. [16][17][18] The limitations of our study must also be noted. An obvious limitation of our study is that we could not control for household wealth in the regression analysis.…”
Section: Resultsmentioning
confidence: 96%
“…These studies have led to mixed findings. While Makela et al (2013) found negative association between social sector spending and child mortality, 18 Deolalikar (2005) found a weak relationship. 16 Bhalotra (2007) found the negative association between public health spending and infant mortality only in rural areas.…”
mentioning
confidence: 99%
See 3 more Smart Citations